Youth in Europe Study (YES!) - Kalter, Frank (Stockholm University, 2016)
Youth in Europe Study (YES!) is the name of the survey study within the project "Children of Immigrants Longitudinal Survey in Four European Countries" (CILS4EU). It is an international research project aimed at gaining more insight into the current living conditions and opinions of young people. The pupil questionnaire covers several areas, including: School and results, Feelings and opinions, Health, Friends and relationship building, Family Relationships and Leisure.

In each participating country, approximately 5,000 pupils attending 8th grade (or corresponding) were interviewed by means of a questionnaire. In Sweden, approximately 130 schools were randomly selected. The first survey in 2011 was followed by another survey in 2012 (when pupils were in 9th grade) one in 2013 (when respondents have finished compulsory school and have entered upper secondary education, the labour market or else)and another​ in 2016.

The survey is conducted in Sweden, Germany, the Netherlands and England. Youth in Europe (YES!) is a joint initiative of researchers from Stockholm University, the University of Mannheim, University of Utrecht, Tilburg University, and University of Oxford.

Purpose:

The purpose of the study is to answer questions on young people’s living conditions and to compare these between countries, e.g.:

Which role do school, family and friends play for youth in Europe?
What are the hobbies, interests and issues they are engaged in?
How do educational careers of young people with and without immigration background proceed? What are their educational and occupational goals?
What can be done in order to improve educational chances of all young people?

Ungdomar i Europa (Youth in Europe Study, YES!) heter enkätstudien inom projektet "Children of Immigrants Longitudinal Survey in Four European Countries" (CILS4EU). Det är ett internationellt forskningsprojekt som görs i Sverige, England, Holland och Tyskland. Studien omfattar flera områden, såsom: Skola, Hälsa, Vänner, Familj, Fritid och Uppfattningar och åsikter.

Studien omfattar ungefär 5 000 elever i varje land, totalt cirka 19 000 elever. Den svenska delen bygger på ett urval om cirka 130 grundskolor. Studien är i grunden longitudinell och eftersom ett av syftena är att studera gymnasievalet följdes den första studien med elever i åttonde klass 2011 upp av en 2012 (när eleverna går i nionde klass) samt ytterligare en år 2013 (när respondenterna går första året på gymnasiet eller har börjat arbeta, alternativt har annan sysselsättning), samt senast år 2016.

Studien är ett samarbete mellan Institutet för social forskning (SOFI) vid Stockholms universitet och universiteten i Mannheim, Utrecht, Tilburg och Oxford.

Syfte:

Syftet med undersökningen är att svara på frågor om ungdomars levnadsvillkor och att jämföra dessa mellan länder, t ex:

Vilken roll spelar skola, familj och vänner för ungdomar i Europa?
Hur ser ungdomars fritid ut?
Hur utvecklas utbildningskarriärer för ungdomar med och utan utländsk bakgrund? Vad har de för framtidsplaner vad gäller utbildning och arbete?
Vad kan man göra för att förbättra ungdomars möjligheter till utbildning?
Youth in Europe Study (YES!)
Children of Immigrants Longitudinal Survey in Four European Countries (CILS4EU)
Keywords: youth; ungdom; youth culture; ungdomskultur; EDUCATION; UTBILDNING; HEALTH; HÄLSA; LABOUR AND EMPLOYMENT; ARBETE OCH SYSSELSÄTTNING; Youth; Ungdomar; Children; Barn; Minorities; Minoriteter; Social Sciences; Samhällsvetenskap; Pedagogy; Pedagogik; Sociology; Sociologi; Other Educational Sciences; Annan utbildningsvetenskaplig forskning